Massage Techniques at Postpartum Spas for Beauty and Wellness Treatments Body in Mombykids Sambong Dukuh Village Jombang District Jombang Regency - Henny Sulistyawati (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Massage is one of the alternative spa beauty postpartum mothers who can maintain the balance of the body to always be healthy and fit. The purpose of this researcher, To describe the process of massage techniques in the body massage of the mother postpartum for the beauty and health of the body and Know how much the client responds to the application.  This type of research is a pseudo-experiment to find out and describe the maternal SPA massage process, using the One-shot case study.  The results of the Mean Massage Technique in postpartum SPA based on 4 aspects that have been observed are 1). The accuracy aspect of preparing 4.00 criteria is very good, 2). Aspects of massage movement technique 3.00 good criteria, 3). Aspects of Punctuality in massage procedure 3.50 criteria are very good, 4 aspects of cleanliness and neatness area 4.00 is very good.  The results of The Massage Technique Process at postpartum SPA for Beauty and Body Health Treatment based on 5 aspects observed, namely: 1). The aspect of stating strongly the amount of pressure given according to posture in the client is 60% category is quite good, 2). Aspect Stipulates comfort level that is felt 100% good category, 3). Aspect stipulates the level of cleanliness on the skin 80% good category, 4). Aspect Stipulates the effect of the results of this massage technique can reduce pain and a soreness 100% good category, 5). Aspect stipulates relaxation effect 100% good category. The response of Massage Technique Respondents at Postpartum SPA for beauty and body health treatments based on 4 aspects observed, 1). The aspect that expresses satisfaction after performing maternal SPA treatment postpartum is 100% good category, 2). Aspects that state the benefits of maternal spa massage techniques for beauty and body health are 100% good category, 3). The aspect that expressed interest in doing advanced SPA treatment postnatal is 75% good category, 4). Recommending in others especially mothers postpartum about maternal SPA treatment postpartum is 100% good category.